Implementation Lean Warehousing Using Waste Assessment Model (WAM) Method - Maulana, Alfin Bima; Ernawati, Dira; Dewi, Sinta (Newinera Publisher, 2025)
Warehouses play an important role in maintaining product quality until the product is delivered to consumers. The many important activities in the warehouse require companies to improve their performance to be effective and efficient in order to maintain trust. ABC Company is a private company engaged in civil construction, landfilling, cut and fill, heavy equipment rental, and spare part distributor. In warehousing activities, there are various activities that don’t have value added or waste. This study aims for identify waste and provide recommendations for improving warehousing activities. The implementation of Lean Warehousing is carried to identifying the warehousing flow process with Value Stream Mapping (VSM), then identifying 7 wastes that occur in the warehousing process using the Waste Assessment Model (WAM) method. The results of the study showed that the waste with the highest percentage level was waste inventory (I) waste overpurchase (O) waste defect (D). From the proposed improvements and Future stream mapping, it was found that the lead time was reduced to 544 minutes, which eliminated 200 minutes of non- value added activity. So that activity increased by 27% from the initial condition.